2019
DOI: 10.1002/mawe.201900050
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the residual stresses of cold full‐forward extruded parts by application of an active counter punch

Abstract: Der Einsatz eines gesteuerten Gegenstempels als aktives Element kann die Qualität und die Beanspruchbarkeit kaltfließgepresster Produkte signifikant verbessern. Durch konventionelle Prozessführung mittels Voll‐Vorwärts‐Fließpressen hergestellte Bauteile weisen hohe Zugeigenspannungen an der Oberfläche sowie einen steilen Spannungsgradienten auf. Neben der Gefahr des Verzugs beeinträchtigt dieser ungünstige Eigenspannungszustand das Ermüdungsverhalten. Von den Autoren wurde ein System entwickelt, das während de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
3
13
0
1
Order By: Relevance
“…230 HV 0.1. This coincides with the literature values of 151.4 HV 0.3 for 1.4307 and 143.3 HV 0.3 for 1.4404 in the annealed state [7]. It is of note that the decay of the hardness is roughly exponential.…”
Section: Section III Unetchedsupporting
confidence: 92%
See 1 more Smart Citation
“…230 HV 0.1. This coincides with the literature values of 151.4 HV 0.3 for 1.4307 and 143.3 HV 0.3 for 1.4404 in the annealed state [7]. It is of note that the decay of the hardness is roughly exponential.…”
Section: Section III Unetchedsupporting
confidence: 92%
“…Section III Section I Figure 6: Microstructure analysis by optical microscopy of sections I and III, V2A-etchant. The initial micrographs can be seen in [7].…”
Section: X 500x 50x 500xmentioning
confidence: 99%
“…Here, the tensile residual stresses on the surface in the steady-state region are reduced from about 750 to about 200 MPa with a constant counter-force of 80 kN. These results were validated by X-Ray diffraction measurements and similar results were obtained for the material 1.4404 [45]. Looking at Fig.…”
Section: Alternative Process Executionsupporting
confidence: 80%
“…For further research in this direction, it is important that residual stress measurements on the surface are reproducible both at the same position as well as for varied measurement positions. The change of the residual stress state of austenitic steels shaped by cold extrusion at various depths has been researched extensively [5,6]. From the surface to depths of 1 mm, changes in the residual stress up to 800 MPa have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is imperative to gain reliable information from measurements at the surface. Research about optimizing the measurement parameters for the difficulties caused by coarsegrained microstructures has already been conducted [5]. In this research, it was shown that the worsening of measurement results by coarse grain effects can be alleviated by choosing a longer exposure time, introducing oscillation and φ-rotation, or utilizing a collimator with a bigger diameter.…”
Section: Introductionmentioning
confidence: 99%